Hyperuricemia as a Risk Factor for Cardiovascular Diseases - Hisatome, Ichiro; Li, Peili; Taufiq, Fikri; Maharani, Nani; Kuwabara, Masanari; Ninomiya, Haruaki; Bahrudin, Udin (Faculty of Medicine, Universitas Diponegoro, 2020)
Serum uric acid level above 7 mg/dl is defined as hyperuricemia, which gives rise to the monosodium urate (MSU), causing gout and urolithiasis. Hyperuricemia is an independent risk factor as well as a marker for hypertension, heart failure, atherosclerosis, atrial fibrillation, and chronic kidney disease. MSU crystals, soluble uric acid (UA), or oxidative stress derived from xanthine oxidoreductase (XOR) might be plausible explanations for the association of cardio-renovascular diseases with hyperuricemia. In macrophages, MSU activates the Nod-like receptor family, pyrin domain containing 3(NLRP3) inflammasome, and proteolytic processing mediated by caspase-1 with enhanced interleukin (IL)-1β and IL-18 secretion. Soluble UA accumulates intracellularly through UA transporters (UAT) in vascular and atrial myocytes, causing endothelial dysfunction ad atrial electrical remodeling. XOR generates reactive oxygen species (ROS) that lead to cardiovascular diseases. Since it remains unclear whether asymptomatic hyperuricemia could be a risk factor for cardiovascular and kidney diseases, European and American guidelines do not recommend pharmacological treatment for asymptomatic patients with cardio-renovascular diseases. The Japanese guideline, on the contrary, recommends pharmacological treatment for hyperuricemia with CKD to protect renal function, and it attaches importance of the cardio-renal interaction for the treatment of asymptomatic hyperuricemia patients with hypertension and heart failure.